Review: endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) - Strong, Andrew T.; Ponsky, Jeffrey L. (Annals of Laparoscopic and Endoscopic Surgery, 2016)
Endoscopic resection within the gastrointestinal tract has changed the disease management paradigm for multiple premalignant conditions. Recently indications have expanded to include several types of early cancers as well. Unified by submucosal injections and a submucosal dissection plane, endoscopic resection techniques are generally divided into endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD). EMR is a natural extension of polypectomy, applied to a flat lesion after a submucosal injection. ESD is a technically more difficult technique that involves tunneling the endoscope into the submucosal plane, but may allow curative, en bloc, resections of early stage malignancies. This review evaluates an array of current evidence for pathologies within the gastrointestinal tract, appropriate preoperative evaluation, preparation and procedural techniques.